The Influence of Customer Engagement and Corporate Reputation on Customer Loyalty through Customer Satisfaction - Dian Kharisma; Aang Curatman (Jurnal Ilmiah Manajemen Kesatuan, 2026)
This study examines customer loyalty in the Indonesian motorcycle spare parts market, focusing on motorcycle body parts, which saw declining sales and rising churn between 2022 and 2024. Although prior research highlights customer engagement, corporate reputation, and customer satisfaction, studies in Indonesia have mostly assessed them separately, limiting insight into their combined impact on customer loyalty. This study aims to analyze both the direct and indirect effects of customer engagement and corporate reputation on customer loyalty through the mediating role of customer satisfaction. A quantitative approach was employed, with data collected from 100 respondents in Cirebon using proportional stratified random sampling and analyzed using Partial Least Squares Structural Equation Modeling. The findings indicate that customer engagement and corporate reputation significantly enhance customer satisfaction, which in turn strengthens customer loyalty, confirming both direct and mediating relationships. These results highlight the central role of customer satisfaction in translating engagement and reputation into sustained loyalty, and provide a comprehensive framework for developing strategies that foster meaningful customer experiences, strengthen organizational credibility, and promote long-term customer loyalty. This study contributes by offering an integrated model that can guide practitioners in improving customer loyalty through a strategic focus on satisfaction.